Regulation of IL4 gene expression by T cells and therapeutic perspectives - Li-Weber, Min; Krammer, Peter H. (Nature reviews. Immunology, 2003)
Interleukin-4 (IL-4) is a key cytokine that controls the differentiation of T helper (TH) cells to the TH2 effector cells that are responsible for cellular immunity and inflammation.Expression of the gene encoding IL-4 by T cells is regulated in two steps — the early stages of T-cell differentiation and the later stage of acute gene expression by differentiated TH2 effector cells.During the first stage, the transcription factor GATA3 (GATA-binding protein 3), which is expressed during TH2-cell differentiation, induces chromatin remodelling at various control regions of the IL4 gene, leading to de-condensation of the IL4 locus.Acute expression of the IL4 gene by differentiated TH2 cells is regulated by many positive and negative inducible transcription factors, such as nuclear factor of activated T cells (NFAT) proteins, AP1, nuclear factor-κB, interferon regulatory factor 1 (IRF1) and other factors that bind the promoter and enhancer elements and coordinately achieve a fine degree of control over the transcriptional activity of the gene.As acute expression of IL-4 by TH2 effector cells has a central role in the pathogenesis of allergic diseases, a better understanding of the regulatory mechanisms for IL4 gene expression might provide greater possibilities to develop therapeutic strategies. Recently, studies with vitamin E, aspirin and parthenolide have shown the potential of intervening at the level of transcription of the IL4 gene.
Gesehen am 02.03.2021